Evaluation of Murabahah Contract from a Sharia Perspective at BPRS in Aceh Province - Fajri, Khairul; Marjulin,; Busra, (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study was to determine the suitability level of murabahah contract practices at BPRS in Aceh Province compared to PSAK No. 102 which includes recording (recognition and measurement), presentation, disclosure, reporting and the eight DSN Fatwas related to murabahah contracts. This research is qualitative in the character, the research method was using by interviews, observation and documentation related to murabahah financing. The results of this study indicate that the variable PSAK No. 102 the average value of all the indicators in PSAK No. 102 the conformity level of each BPRS in Aceh Province is above 90%, the lowest percentage of conformity level is 92% and the highest is 97%.  The variable of DSN Fatwa the average value for obtaining the percentage of conformity levels varies greatly, starting from the lowest percentage is 48% and the highest for each BPRS in Aceh Province, reaching an average value of 90%, and then in the financial reports of BPRS in Aceh Province, all accounts related to murabahah transactions. The implications of murabahah practices based on PSAK No. 102 and the DSN Fatwa for BPRS in Aceh Province that is not fully compliant will be indicated as riba and murabahah buying and selling is not valid according to sharia.